Preferences in the Selection of Specialization Courses by the Students of German Department Class of 2017 State University of Malang - Yaniar Dian Rahayu (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2021)
The aim of this research is to describe the opinion of the Student German Department Class of 2017 about the specialization courses provided and to describe the factors behind the selection of specialization courses. In this research used the descriptive and qualitative method. The technique of the data collection were interview and documentation. The interview guidelines are used to collect the opinion of the Student about the specialization courses provided and the factors behind the selection of specialization courses. The documents used to collect the factors behind the selection of specialization courses. The collected data is reduced, written in the form of narrative text, and conclusions are drawn to answer the problem formulation.The result of this research showed that the specialization courses are varied and complete. And then the specialization courses can be used for self-development. The factor behind the selection of specialization courses are experience, interest, and talent.